(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
PESA is inventive because it legally recognizes theability of tribal communities to reinforce their own systems of self-governanceor create new legal spaces that can not only reverse centuries of externalcultural and political offensive but can also create the prospects to controltheir own destiny. The Gram Panchayats in Koraput district becomes the important,endowed with significant powers